Dasar Hukum dan Pertimbangan Hakim Dalam Memutus Permohonan Izin Poligami Karena Istri Tidak Bisa Menjalankan Kewajiban: Analisis Putusan Hakim Pengadilan Agama Purworejo No. 0090/Pdt.G/2018/PA.Pwr - Widiyanto, Hari (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
Abstract Marriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the Godhead. (Article 1 of the Marriage Law). Marriage is one of the religious commands to his servants who are able to immediately carry it out. Because marriage can prevent immorality, both in the form of vision and in the form of adultery. One purpose of marriage is to connect descendants who will later be made heirs. In Islam it is permissible for a Muslim man to marry two to four women, if he can and is able and able to maintain and be fair to his wives in providing a living and time distribution. If you are worried that you will not be able to act fairly, then you should marry someone.Polygamy is a marriage between a man and more than one woman at the same time. Until now, polygamy in Indonesia is still a hot topic for research. The evocative performance of the concept, and the support of the rise of polygamy practices, does not seem to have brought a variety of counter-productive views in the community. The emergence of various dilemmatic perceptions, of course one of them starts from the reasons that are the basis of polygamy, as well as the mode adopted by polygamists.Based on the author's research, if there is a Court decision on the Request for Polygamy because the Wife Cannot Carry Out His Obligations as a Wife, then the issue is what is the legal basis and consideration of the judge in deciding the case for a polygamy request because the Wife Cannot Carry Out His Obligatory Analysis of the Decision of the Purworejo Religious Court Judge No. 0090 / Pdt.G / 2018 / PA.Pwr.